Oncological outcomes following extreme oncoplastic breast conserving surgery (eOPBCS) for locally advanced breast cancer (LABC): A systematic review and meta-analysis - Megan Chua Wern Ee; Ashley Lee Shi Hui; Wong Hung Chew; Emmeline Elaine Cua-Delos Santos; Sean Li Siwei; Sng Ming Xian; Qin Xiang Ng; Serene Goh Si Ning (Breast)
Introduction: Locally advanced breast cancer (LABC) accounts for 5 % of new breast cancer diagnoses in developed countries and 30–60 % in developing regions. Historically, treatment relied on mastectomy guided by the Halstedian theory. Advances in neoadjuvant chemotherapy (NACT), breast-conserving surgery (BCS), and radiation have transformed treatment into a multimodal approach. Extreme oncoplastic BCS (eOPBCS) has expanded the boundaries of BCS, enabling large-volume resections with breast reshaping. However, its oncologic outcomes compared to mastectomy remain unclear, particularly in LABC. Methods: A systematic review and meta-analysis were conducted following PRISMA guidelines (PROSPERO: CRD42024535182). Studies involving eOPBCS for LABC were reviewed, and those comparing outcomes with mastectomy were included in the meta-analysis. The primary outcomes were overall survival (OS), disease-free survival (DFS), and local recurrence rates (LRR). Data were synthesized using a random-effects model. Results: Of 866 identified studies, 33 were included in the systematic review and 4 in the meta-analysis, involving 2902 patients with LABC. Among them, 16.1 % underwent eOPBCS. Patients receiving eOPBCS were younger, had larger tumours, and more frequently underwent axillary clearance. The pooled hazard ratio (HR) for OS comparing mastectomy to eOPBCS was 1.72 (95% CI 1.04-2.83). Meanwhile, HRs for DFS (1.11, 95% CI 0.60-2.08) and LRR (0.67, 95% CI 0.38-1.18) showed that there were no statistically significant differences but a trend toward lower recurrence rates with mastectomy. Conclusion: eOPBCS demonstrates comparable to superior oncological outcomes to mastectomy in LABC, offering a promising option for selected patients. However, slightly elevated local recurrence rates, though not statistically significant, highlight the importance of careful patient selection and further research. High-quality prospective studies are essential to validate these findings and refine criteria for incorporating eOPBCS into routine clinical practice.